"Watching the tsunami come": A case study of female healthcare provider experiences during the COVID‐19 pandemic. Issue 4 (30th April 2021) - Austin, Elizabeth J.; Blacker, Alexandria; Kalia, Isha
Abstract: As health systems rapidly respond to COVID‐19, it is unclear how these changes influence the experiences and well‐being of female healthcare providers (FHCPs), including the potential for FHCPs to develop compassion fatigue and secondary traumatic stress. We conducted qualitative interviews ( n = 15) with FHCPs at three locations (Washington, California, and New York). Interviews explored FHCP's perspectives on how care delivery changed, processes of information delivery and decision‐making, gender inclusion, and approaches to managing stress and well‐being. An inductive coding process was used to generate themes. FHCPs described significant changes to the way they delivered care, and their work environments, during the COVID‐19 pandemic. Five themes emerged that characterized the experiences of FHCPs during COVID‐19, including conflicting feelings while providing care, managing information and decisions, balancing roles, coping and well ‐ being, and considerations for moving forward . FHCPs experienced many impacts to their professional and personal lives during COVID‐19 that further complicated their ability to manage stress and well‐being. The themes identified through this work offer important lessons about how to support the well‐being of FHCPs and signify the widespread potential for compassion fatigue among FHCPs as a result of COVID‐19.